Liveable urban forms: planning, self-organisation, and a third way (Isobenefit urbanism) - D’Acci, LS; Banister, D; White, RW (Springer Nature [academic journals on nature.com], 2024)
Urban development combines the forces of dispersal and agglomeration, often facilitated by free market forces, and this results in different patterns and self-organised ways, with both positive and negative outputs. Globally, over 6 billion people will live in cities by 2050, and this would require at least an additional 1.2 million km2 land to be built on. This huge expansion of the urban population and area requires construction at scale that avoids current urban problems such as urban heat island effects, carbon emissions, pollution, congestion, urban sprawl and excessive hard surfacing, while maintaining the physical and mental quality of life. Two basic approaches would be to let market forces freely shape our new urban areas or to impose a strong planning framework. This paper introduces a third way, Isobenefit urbanism that takes advantage of the two basic approaches to urban development. Isobenefit urbanism is a relatively recent urban development approach to shaping urban form, through an examination of centralities and localisation by a code whose implementation results in Isobenefit cities where one can walk to reach the closest centrality (where theatres, restaurant, schools, offices, promenades, shops…are located) and the closest access to green land regardless where one lives, and regardless the size of the city.